Fish Marketing Decision Support System at Belawan Fishing Port with AHP and PROMETHEE Method - Wildani Wildani; Muhammad Dedi Irawan (Universitas Bandar Lampung (UBL), 2025)
This study aims to develop a fish marketing decision support system at Belawan Fishing Port to assist fish warehouses or markets in determining the vessels with the best fish marketing performance. Once the results are obtained, port authorities can evaluate vessels with low marketing results to improve their marketing strategies in the future. The methods used in this study are the Analytical Hierarchy Process (AHP) and PROMETHEE, which are applied to evaluate and rank marketing alternatives based on multiple criteria such as market demand, price, sales volume, sales targets, and sales turnover. The integration of these two methods allows for a more structured and objective decision-making process. The results of the study show that the application of the AHP and PROMETHEE methods can effectively assist in determining optimal marketing decisions by comprehensively considering the factors that influence fish marketing performance. This system also increases the accuracy of decision making by up to 90% compared to conventional methods that rely solely on experience. Overall, the developed system is expected to improve the efficiency of fish marketing and support the welfare of fishermen in Belawan Fishing Port.